Nilai Pendidikan Akhlaq tentang Sikap dalam Persfektif Islam - Devy Habibi Muhammad; Fitria Anggraeni; M Jadid Khadavi (Edumaspul: Jurnal Pendidikan, 2022)
The Qur'an not only provides guidelines for the life of a particular group, but also covers all aspects of human life, both related to Allah SWT, the relationship between humans and the universe. The Koran contains many values ​​about moral education, such as God's command for justice in Surah An-Nahl verse 90, and Surah Al-Maidah verse 8. Law, health, family, including education. Therefore, the writer is interested in analyzing these two surahs about justice. The formulation of the problem raised in this study is about the value of moral education of the Koran (explanatory research on the Koran surah an Nahl verse 90 and al maidah verse 8). The method used in this research is library research with qualitative descriptive analysis technology, namely by obtaining data or materials related to the topic of discussion and the problem from the library, then using the Tahlili Method analysis, which is a method of interpretation to explain the contents of the Koran from all aspects. aspect. The results showed that Surah an Nahl verse 90 contains the value of moral education about justice, including all forms of justice, including justice for oneself, law, justice for family, relatives and enemies. At the same time, in verse 8 of Surah al-Maidah, Allah's command is a just witness for the enemy.